Jatropha curcas L. Leaf Extract Effects on Blood Pressure and Lipid Levels in Hypertensive Rats with High-Fat Diet - Moch. Saiful Bachri; Wiki Yuli Anita; Putri Dwi Lestari; Desi Eko Wulansari; Dwi Retno Nengtyas; Muhammad Ma'ruf; Sapto Yuliani; Wahyu Widyaningsih; Laela Hayu Nurani; Daru Estiningsih; Vivi Sofia (Universitas Airlangga, 2024)
Background: One of the main risk factors for cardiovascular diseases such as coronary atherosclerotic heart disease (CAHD) is dyslipidaemia or high levels of low-density lipoprotein (LDL) and triglycerides (TG) and low levels of high-density lipoprotein (HDL). Hypertension is also a cause of cardiovascular disease. One potential plant to lower LDL levels and blood pressure is Jatropha curcas, which is known to contain saponins, polyphenols, and flavonoids. Objective: The purpose of this study was to determine the effect of the ethanol extract of Jatropha curcas leaves (EEJCL) on blood pressure, LDL levels, and HDL levels in hypertensive rats given a high-fat diet. Methods: This study is an experimental study with a pretest-posttest control group design on male Wistar strain rats. Rats were divided into seven groups, namely the normal group, control group (induced with NaCl and given a high-fat diet), Captopril group, Simvastatin group, and EEJCL groups given doses of 1.8, 2.7, and 4.05 g/kg BW. The data obtained were analysed using the One-Sample Kolmogorov-Smirnov Test, Homogeneity of Variance, One-Way ANOVA, and Tukey Test. Results: The results showed that the administration of EEJCL could significantly lower LDL levels and blood pressure and increase HDL levels (p < 0.05) at doses of 1.8, 2.7, and 4.05 g/kg BW, and the dose of 4.05 g/KgBW was the most optimal dose. Conclusion: EEJCL has a potential for development in the treatment of hypertension and dyslipidaemia.